Evolution of the structural phase and orientation in ultrathin SrRuO3 film with SrTiO3 capping layer - Akhilesh Kr. Singh; Song Yang; Uddipta Kar; Guan-Ruei Chen; Shih-Chang Weng; Chia-Hung Hsu; Wei-Li Lee (Scientific Reports)
Abstract In a perovskite oxide of $$\text {ABO}_3$$ , the $$\text {BO}_6$$ octahedral rotation and tilting are known to result in a structural distortion and transform the crystalline structure to a lower symmetry phase, such as the tetragonal phase (T-phase) and distorted orthorhombic phase (O-phase). Here, we present the observation of such structural transformation in 6 unit cell (uc) ultrathin films of $$\text {SrRuO}_3$$ (SRO) driven by an additional $$\text {SrTiO}_3$$ (STO) capping layer. A series of nominal STO (x uc)/SRO (6 uc) films with x ranging from 0 to 8 were grown on STO (001) substrates using an oxide molecular beam system with adsorption-controlled growth technique for SRO and layer-by-layer growth technique for STO. Systematic high-resolution X-ray diffraction measurements revealed a clear transition from the T-phase for x = 0 to the O-phase for x = 2 and 8, which was accompanied by a change of the structural orientation from (001)-oriented SRO in T-phase to (110)-oriented SRO in O-phase. Our findings highlight the possibility of intriguing interface-driven structural phase and orientation transformations in a perovskite oxide system.